Isolation And Characterization Of Bacteriophage From Raw Sewage Specific For Escherichia coli O157:H7 - Juharul Zama, Siti Fariza (2014)

(untitled)
E. coli O157:H7-specific phage was successfully isolated for the first time in Malaysia, from a sewage facility of Universiti Sains Malaysia campus in Penang. Based on morphological study, the isolated phage was suggested to be a T4-like phage belonging to Myoviridae family; similar to other E. coli O157:H7-specific phages previously isolated. Faj khusus pada E. coli O157:H7 telah berjaya diasingkan untuk pertama kalinya di Malaysia dari kemudahan sisa kumbahan dalam kampus Universiti Sains Malaysia di Pulau Pinang. Berdasarkan kajian morfologi, faj ini dipercayai adalah faj-menyerupai T4 yang tergolong dalam keluarga Myoviridae; begitu juga seperti faj khusus pada E. coli O157:H7 lain yang pernah diasingkan sebelum ini.